Proposal for a Blockchain-Based Model for Data Management in Maritime Education and Sector Stakeholder Institutions - KAPETANOVIĆ, Vera; KRČUM, Maja; KRSTAJIĆ, Božo (Promet - Traffic&Transportation, 2026)
Blockchain technology is increasingly proving to be an innovative solution in numerous spheres of the economy, including education, and by extension, institutions involved in Maritime Education and Training (MET). As MET institutions face increasing challenges, such as managing and maintaining large databases, extensive record-keeping, and exchanging and processing information, the application of this technology is emerging as a response to these challenges. In addition to the fact that it would lead to the digitalisation of documents, the application of the technology would, above all, improve the security and reliability of documentation. Owing to its decentralised, transparent and immutable nature, blockchain technology offers a comprehensive framework for overcoming these challenges within MET institutions. The objective of this paper is to propose a model for the application of blockchain technology in MET institutions in order to address the lack of a unified, secure and transparent data system shared by all stakeholders involved in maritime education and training. This paper provides a comprehensive review of the literature on the application of blockchain technology in the maritime industry, highlighting its potential for improving data management and operational efficiency. Furthermore, the paper proposes the implementation of blockchain technology, focusing on the creation of an integrated database that would be used by various users, including MET institutions, state administration (ministries, port authorities), seafarer training centres, maritime agencies, medical institutions and seafarers themselves. Moreover, the paper offers detailed recommendations and guidelines for implementing the hybrid model in MET institutions, with a special emphasis on its role in automating administrative processes through smart contracts, enhancing transparency, and improving overall document security.